2019
DOI: 10.2478/raon-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

The use of high-frequency short bipolar pulses in cisplatin electrochemotherapy in vitro

Abstract: Background In electrochemotherapy (ECT), chemotherapeutics are first administered, followed by short 100 μs monopolar pulses. However, these pulses cause pain and muscle contractions. It is thus necessary to administer muscle relaxants, general anesthesia and synchronize pulses with the heart rhythm of the patient, which makes the treatment more complex. It was suggested in ablation with irreversible electroporation, that bursts of short high-frequency bipolar pulses could alleviate these problems. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 63 publications
(98 reference statements)
0
36
0
Order By: Relevance
“…showed complete resealing of plasma membrane 10 minutes after pulse treatment using 8 x 100 μs pulses. 63 Thus, another time point for ATP measurement was chosen, i.e . 15 minutes after ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…showed complete resealing of plasma membrane 10 minutes after pulse treatment using 8 x 100 μs pulses. 63 Thus, another time point for ATP measurement was chosen, i.e . 15 minutes after ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The third large area of preclinical research is dealing with different types of electrodes that can be used in vitro, in vivo, or in humans, that is, grid, single needle, or endoscopic, [59][60][61][62][63][64] with different types (e.g., sine wave pulses, pulsed electromagnetic field, and high-frequency short bipolar pulses), and parameters of electric pulses (amplitude and frequency). [65][66][67][68][69] The overall aim of these studies is to provide new electrodes that will be able to reach/treat the tumors that are not accessible with the current electrodes that are on the market and to provide electrodes that will not induce pain, muscle contraction, and/or skin burns, that is, undesired side effects that are commonly reported in clinical studies on electrochemotherapy. Another approach to foster and push forward electrochemotherapy is advanced numerical modeling of treatment, either in vitro or in vivo, to elucidate parameters that can influence the treatment outcome or to provide feasibility studies for future perspective electrochemotherapy treatment of tumors.…”
Section: Electrochemotherapy: New Electrodes and Numerical Modelingmentioning
confidence: 99%
“…For instance, in almost all the electrochemotherapy treatments, eight pulses are applied instead of one (Silve et al 2014). As another example, it has been demonstrated, that in case of irreversible electroporation, the transmembrane voltage threshold for a single 1 μs long pulse is 2.1 times higher in comparison with the bursts of 100 μs long pulses (Sano et al 2015;Scuderi et al 2019). In addition, number of studies have confirmed, that the effects of electroporation are not only depended on the number of pulses applied, but in general the electroporation is a frequency-dependent phenomena (Silve et al 2014;Sano et al 2014;García-Sánchez et al 2018;Bhonsle et al 2018;Novickij, Ruzgys, Grainys, et al 2018;De Angelis et al 2019).…”
Section: Number Of Pulses and Repetition Frequencymentioning
confidence: 99%